2009
DOI: 10.1007/s00423-009-0537-1
|View full text |Cite
|
Sign up to set email alerts
|

Management of isolated spontaneous dissection of superior mesenteric artery

Abstract: Patients with symptoms lasting for more than 1 week, aneurysmal dilatation more than 2 cm in diameter, and SMA stenosis are suitable candidates for surgical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 23 publications
(40 reference statements)
0
64
0
Order By: Relevance
“…The SMA dissection morphology was classified as described above by Sakamoto, et al 2) and Zerbib, et al 3) Yun, et al 10) classified the morphology into type I (the same as that classified by Sakamoto, et al), type II (cases with no re-entry, the false lumen is patent [IIa] and occluded [IIb]), and type III (occluded). We adopted the more detailed classification established by Sakamoto, et al and Zerbib, et al It is considered desirable to perform active treatment, such as surgical and endovascular treatments, when the diameter is 2 cm or greater or stenosis is 70% or more in cases of types II, III, V and VI of this classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SMA dissection morphology was classified as described above by Sakamoto, et al 2) and Zerbib, et al 3) Yun, et al 10) classified the morphology into type I (the same as that classified by Sakamoto, et al), type II (cases with no re-entry, the false lumen is patent [IIa] and occluded [IIb]), and type III (occluded). We adopted the more detailed classification established by Sakamoto, et al and Zerbib, et al It is considered desirable to perform active treatment, such as surgical and endovascular treatments, when the diameter is 2 cm or greater or stenosis is 70% or more in cases of types II, III, V and VI of this classification.…”
Section: Discussionmentioning
confidence: 99%
“…Zerbib, et al 3) added type V accompanied by dissection and stenosis of the SMA and type VI with partial or complete occlusion (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…[18][19] Endovascular or surgical treatment should be performed in cases after failure of conservative treatment, presenting persistent abdominal symptoms, and intestinal ischemia and rupture of the artery. [20][21] In our study, most patients accepted conservative treatment and obtained a favorable outcome except 5 who underwent endovascular intervention. The true lumen stenosis degree was more than 75%…”
Section: Discussionmentioning
confidence: 62%
“…8) Sakamoto reported that one patient with type II needed urgent surgery because of small bowel ischemia and 11 other patients were treated conservatively. Zerbib et al 9) proposed a modified classification: type I − IV of Sakamoto's classification; type V, aneurysmal dissection with stenosis of the distal part of the SMA; and type VI, total [VIa] or partial [VIb] thrombosis of the SMA. Most patients of type I respond to conservative treatment but need long time follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…9) We experienced ten patients with SMA dissection during the past 7 years. Among the ten there was no intervention due to risk of rupture at acute or subacute onset periods.…”
Section: Discussionmentioning
confidence: 99%